Systematic literature review of learning curves for colorectal polyp resection techniques in lower gastrointestinal endoscopy. (30th January 2020) - Rajendran, A.; Pannick, S.; Thomas‐Gibson, S.; Oke, S.; Anele, C.; Sevdalis, N.; Haycock, A.
Abstract: Aim: The performance of therapeutic procedures in lower gastrointestinal endoscopy (LGI) can be challenging and carries an increased risk of adverse events. There is increasing demand for the training of endoscopists in these procedures, but limited guidelines exist concerning procedural competency. The aim of this study was to assess the learning curves for LGI polypectomy, colorectal endoscopic mucosal resection (EMR) and colorectal endoscopic submucosal dissection (ESD). Method: A systematic review of electronic databases between 1946 and September 2019 was performed. Citations were included if they reported learning curve data. Outcome measures that defined the success of procedural competency were also recorded. Results: A total of 34 out of 598 studies met the inclusion criteria of which 28 were related to ESD, three to polypectomy and three to EMR. Outcome measures for polypectomy competency ( en bloc resection, delayed bleeding and independent polypectomy rate) were achieved after completion of between 250 and 400 polypectomies and after 300 colonoscopies. EMR outcome measures, including complete resection and recurrence, were achieved variably between 50 and 300 procedures. Outcome measures for ESD included efficiency (resection rates and procedural speed) and safety (adverse events). En bloc resection rates of over 80% and R0 resection rates of over 70% were achieved at 20–40 cases and procedural speed increased after 30 ESD cases. Competency in safety metrics was variably achieved at 20–200 cases. Conclusion: There is a paucity of data on learning curves in LGI polypectomy, EMR and ESD. Despite limited evidence, we have identified relevant outcome measures and threshold numbers for the most common LGI polyp resection techniques for potential inclusion in training programmes/credentialing guidelines.